Privacy and exposure: domestic tragedy in early modern England - O'Brien, Emily (Trinity College Dublin. Long Room Hub, 2008)
The genre of domestic tragedy emerged during a period in which the burgeoning ideology of private life was matched by active publication of cheap printed texts offering sensational 'news' stories. This research project identifies an ambivalence between a cultural desire for privacy and a desire for exposure of others' privacy, and situates the genre of domestic tragedy within this.
Exhibited at the Glucksman Memorial Symposium on June 12th 2008
Keywords: Drama -- early modern England; Tragedy -- domestic; Murder -- representation of; Print culture -- early modern